Theranostic Cancer Treatment Using Lentinan-Coated Selenium Nanoparticles and Label-Free CEST MRI - Guanfu Liu; Jiabao Ling; Lizhen He; Yuan Xu; Tianfeng Chen; Changzheng Shi; Liangping Luo (MDPI AG, 2022)
Selenium nanoparticle (SeNP)-based nanotherapeutics have become an emerging cancer therapy, while effective drug delivery remains a technical hurdle. A theranostic approach, through which imaging companions are integrated with SeNPs, will allow image-guided drug delivery and, therefore, is highly desirable. Traditional methods require the chemical conjugation of imaging agents to the surface of nanoparticles, which may impede the later clinical translation. In this study, we developed a label-free strategy in which lentinan-functionalized SeNPs (LNT-SeNPs) are detected using MRI by the hydroxyl protons carried on LNT molecules. The in vitro phantom study showed that LNT and LNT-SeNPs have a strong CEST signal at 1.0 ppm apart from the water resonance, suggesting an in vivo detectability in the µM concentration range. Demonstrated on CT26 colon tumor cells, LNT-SeNPs exert a strong anticancer effect (IC50 = 4.8 μM), prominently attributed to the ability to generate intracellular reactive oxygen species. However, when testing in a mouse model of CT26 tumors, administration of LNT-SeNPs alone was found unable to deliver sufficient drugs to the tumor, leading to poor treatment responses. To improve the drug delivery, we co-injected LNT-SeNPs and TNF-α, a previously reported drug that could effectively damage the endothelial cells in the tumor vasculature, thereby increasing drug delivery to the tumor. Our results revealed a 75% increase in the intratumoral CEST MRI signal, indicating a markedly increased delivery efficiency of LNT-SeNPs when combined with TNF-α. The combination therapy also resulted in a significantly enhanced treatment outcome, as revealed by the tumor growth study. Taken together, our study demonstrates the first label-free, SeNP-based theranostic system, in which LNT was used for both functional surface coating and CEST MRI signal generating. Such a theranostic LNT-SeNP system is advantageous because it requires chemical labeling and, therefore, has high biocompatibility and low translatable barriers.